SPECT and EEG in Landau-Kleffner Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Five right-handed children with Landau-Kleffner syndrome (LKS) were studied with EEG and single-photon emission computed tomography (SPECT) before and after 6 months of corticosteroid therapy at the Universities of Estadual de Campinas and Sao Paulo, Brasil.